1999
DOI: 10.1001/archneur.56.3.334
|View full text |Cite
|
Sign up to set email alerts
|

Progression of Parkinsonian Signs in Parkinson Disease

Abstract: In this cohort, the progression of EPSs in PD occurred at a rate of 1.5% per year and at twice that rate among those who died. Bradykinesia, rigidity, and gait and balance impairment worsened at similar rates, whereas tremor did not, suggesting that tremor may be relatively independent of these other cardinal manifestations of PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
159
6
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 189 publications
(192 citation statements)
references
References 23 publications
25
159
6
2
Order By: Relevance
“…The choice of three latent variables corroborates the literature (9,13,14). In Parkinson disease clinical trials, the initiation time of PD medications is closely related to the rate of disease progression.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The choice of three latent variables corroborates the literature (9,13,14). In Parkinson disease clinical trials, the initiation time of PD medications is closely related to the rate of disease progression.…”
Section: Discussionsupporting
confidence: 71%
“…When analyzed independently, tremor items have been shown to progress more slowly than all other motor features (9,13,14). Non-motor symptoms occur a decade before the other symptoms (16).…”
Section: Introductionmentioning
confidence: 99%
“…13 As a perspective for our results, in a large community-dwelling cohort of Parkinson disease patients, annual increases for bradykinesia, gait/balance, and rigidity ranged from 2 to 3.1%, but tremor did not change. 28 Annual increase of the total MOSI score was 1.5% in that study as compared with 3% in the current one. However, direct comparison of these two rates is confounded by use of part of the UPDRS in our cohort, different baseline levels of MOSIs, and treatment with dopaminergic agents.…”
Section: Discussioncontrasting
confidence: 46%
“…A recent PET study suggests that the metabolic pattern of tremor-dominant PD is significantly different from that of akinesia/rigidity-dominant PD (Mure et al, 2011). Patients with tremor-dominant PD exhibit better clinical prognoses and slower disease progression with less cognitive decline (Louis et al, 1999;Marras et al, 2002;Rajput et al, 2009). Using FDG-PET, Mure et al (2011) indicated that these clinical findings correlate with a slow deterioration of the metabolic pattern in patients with tremor-dominant PD.…”
Section: Positron Emission Tomography (Pet) and Single Photon Emissiomentioning
confidence: 99%